Computers in Education: What for? - Eevi E. Beck (Universitetsforlaget, 2011)
The assumption that increased use of computing technologies is beneficial per se has been questioned in research on workplace computing since the early 1970ies. It is interesting, then, to note how easily such assumptions have become part of the landscape within Education research. The intention of this paper is to encourage stopping and pausing to consider what is happening (an empirical question), and whether what is seen is desirable (a normative question). The paper calls for more debate (among researchers, teachers, parents, school leaders, governmental bodies, and other interested parties) as to what we would want computers for and how to get there. Points of view would differ; possibly never fully settling on agreement. This would constitute an ideal and a practice of attempting to bring Bildung and democracy to computing use in education, and would be a worthwhile lead to equip the young for participation in a technology-intensive society. The issue should be addressed, however, taking into account critiques of normative approaches. In particular, incorporating insight from research which critically examines ways in which scientific truths and their technical counterparts become established, would aid an understanding of why and how obstacles exist. Such a broad exploration would imply further questions about how the maintenance of boundaries between scientific approaches affects applied questions such as the one posed in the title. This paper, then, carries a two-level argument.